Age‐dependent variation in the terminal investment threshold in male crickets. (1st March 2018) - Duffield, Kristin R.; Hampton, Kylie J.; Houslay, Thomas M.; Hunt, John; Rapkin, James; Sakaluk, Scott K.; Sadd, Ben M.
Abstract: The terminal investment hypothesis proposes that decreased expectation of future reproduction (e.g., arising from a threat to survival) should precipitate increased investment in current reproduction. The level at which a cue of decreased survival is sufficient to trigger terminal investment (i.e., the terminal investment threshold ) may vary according to other factors that influence expectation for future reproduction. We test whether the terminal investment threshold varies with age in male crickets, using heat‐killed bacteria to simulate an immune‐inducing infection. We measured calling effort (a behavior essential for mating) and hemolymph antimicrobial activity in young and old males across a gradient of increasing infection cue intensity. There was a significant interaction between the infection cue and age in their effect on calling effort, confirming the existence of a dynamic terminal investment threshold : young males reduced effort at all infection levels, whereas old males increased effort at the highest levels relative to naïve individuals. A lack of a corresponding decrease in antibacterial activity suggests that altered reproductive effort is not traded against investment in this component of immunity. Collectively, these results support the existence of a dynamic terminal investment threshold, perhaps accounting for some of the conflicting evidence in support of terminal investment.